Содержание и кормление овец - Воробьев Павел Андреевич (Библиотечка "Домашнее животноводство", 1981)
Экземпляры: (20181012) / Инвентарный номер: 3868 / Цена: 0.35 / Сис.шифр: 636.3 / Авт.знак: В75 / ББК: 636.3-04